DETECTING TAX CRIMES IN REPUBLIC OF SERBIA - Pisarić, Milana (Glasnik Advokatske komore Vojvodine, 2025)
The detection of tax crimes is the responsibility of the Tax Administration, as an administrative body within the Ministry of Finance, and these tasks are performed by the Tax Police. The actions of the Tax Police are functionally related to the tax control process, in which it is possible to learn that there are grounds for suspecting that a tax crime has been committed. Tax inspectors, who perform tax control, and Tax Police inspectors are powered to take certain measures and actions to collect information and evidence for tax crimes. The paper analyzes the legal framework for powers of those authorized officials of the Ministry of Finance in detecting tax crimes.